A Theoretical Overview of Unlearning in Engineering - MOONEY, ROBIN (My University, 2016)
Unlearning is the deliberate undoing or reversal of what has been previously learned. This skill has been acknowledged in business and academia as being increasingly important for engineers in a highly changeable 21st century environment; additionally, industry have recently flagged a real-world skill deficit in graduates that can be remedied using the concept of unlearning. This paper shows that modern learning theories and engineering teaching initiatives implicitly rely on unlearning to successfully influence and appropriately prepare engineering students for industry.
PUBLISHED
Keywords: Research Subject Categories::NATURAL SCIENCES; International Development; CDIO; Higher Education; STEM EDUCATION; unlearning